Usaha Peningkatan Kualitas pH Air dan Monitoring Berbasis Mikrokontroller pada Budidaya Ikan Mujaer di Desa Brumbun Kecamatan Maduran Kabupaten Lamongan - Ali, Mukti; Abidin, Zainal (Jurnal EnviScience (Environment Science), 2019)
The aquaculture business is one of the businesses in the fishery sector that is very important in exploiting natural resources and improving the welfare of the community. The detailed studies are needed from the initial selection of fish seedlings, cultivation management and post-harvest management. Brumbun Village is one of the villages that have potential for aquaculture businesses, especially freshwater fish cultivation, especially tilapia. The village government is planning to develop the cultivation of tilapia fish as one of the leading village communities. However, there are several problems, especially in the quality of water used for cultivation purposes, the pH value of water is still around 4-5 so it must be increased to 7-8. Supporting this effort requires efforts to intensify fisheries cultivation, water management and efforts to maintain water quality. 328 microcontroller is used as a tool to monitor the process of improving water quality (pH) and also scheduling feeding on tilapia fish farming.Â Keywords: aquaculture, tilapia fish, monitoring, microcontroller